First zoeal stage of the crab Domecia acanthophora (Desbonne, in Desbonne & Schramm, 1867) (Decapoda, Brachyura) and revision of the larval morphology of superfamily Trapezioidea - Rodrigues Alves, Douglas Fernandes [UNESP]; Farinelli Pantaleao, Joao Alberto [UNESP]; Barros-Alves, Samara de P. [UNESP]; Costa, Rogerio Caetano da [UNESP]; Cobo, Valter Jose [UNESP] (Soc Brasileira Carcinologia, 2016)
The morphology of the first zoeal stage of Domecia acanthophora (Desbonne, in Desbonne & Schramm, 1867) was described from laboratory-hatched material obtained from ovigerous females collected at Vitoria Island on the southeastern Brazilian coast. We compared the larval morphology (zoea I) of fourteen species of the superfamily Trapezioidea, which Domecia glabra Alcock, 1899 is the only congeneric representative of the species described in this study. The morphological characteristics of the first zoea that distinguish D. acanthophora from D. glabra are: three aesthetascs on the exopod antennule; three pairs of lateral spines on carapace; bilobed basial endite of maxilla, with four plumodenticulate setae on each lobe; and telson furcae distally spinulated. It also provides information that may enhance some phylogenetic hypotheses within Trapezioidea crabs.
Keywords: Domeciidae; larval description; southeastern Brazil; Tetraliidae; Trapeziidae